Reconsidering The Mandatory Use Of Indonesian Language In Private Commercial Contract - Suyudi, Aria; Budi, Henry Soelistyo (Global Legal Review, 2022)
A decade after the enactment of Law Number 24 Year 2009 on the Flag, Language and Coat of Arms and Anthem which introduces mandatory use of Indonesian language in memorandums of understanding or agreements involving state institutions, government agencies, Indonesian private institutions or Indonesian citizens, there are still many questions arised about the extent of which these norms should apply in the private commercial sphere.  Various litigations filed before the court to declare the agreement null and void for failure to meet the language provisions. While some lawsuit has been successful, but more recent court decisions have been consistently rejecting petition to declare an agreement as null and void for failure to comply with article 31 Law Number 24 Year 2009.This paper will conduct a normative study to determine the extent of which the mandatory use of the Indonesian language in the agreement has affect the private commercial sphere. In what instance violation of the provision has been fully regarded as violation of an Objective Condition for a valid agreement as regulated in Article 1320 of the Civil Code which makes the agreement null and void by law and what does not.This paper will study the laws and regulations related to the mandatory use of the Indonesian language in private commercial contracts to find out about situation and study its implementation in selected court decisions to understand the situation and provide possible recommendation for improvements